CoMap: Mapping contagion in the euro area banking sector - Giovanni Covi; Mehmet Ziya Gorpe; Christoffer Kok Sørensen (European Central Bank (ECB), 2019)
This paper presents a novel approach to investigate and model the network of euro area banks' large exposures within the global banking system. Drawing on a unique dataset, the paper documents the degree of interconnectedness and systemic risk of the euro area banking system based on bilateral linkages. We then develop a Contagion Mapping (CoMap) methodology to study contagion potential of an exogenous default shock via counterparty credit and funding risks. We construct contagion and vulnerability indices measuring respectively the systemic importance of banks and their degree of fragility. Decomposing the results into the respective contributions of credit and funding shocks provides insights to the nature of contagion which can be used to calibrate bank-specific capital and liquidity requirements and large exposures limits. We find that tipping points shifting the euro area banking system from a less vulnerable state to a highly vulnerable state are a non-linear function of the combination of network structures and bank-specific characteristics.
Keywords: D85; G17; G33; L14; 330; Systemic Risk; Network Analysis; Interconnectedness; Large Exposures; Stress Test; Macroprudential Policy